Appointing a non-Muslim as arbitrator in tahkim proceedings: polemics, perceptions and possibilities - Idid, Syed Ahmad; Oseni, Umar Aimhanosi (LexisNexis, 2014)
With the skyrocketed increase in social and commercial intercourses among people of diverse racial, religious and cultural backgrounds in the modern world, the world is gradually shrinking into a global hamlet. The implication of this trend in various disciplines has encouraged parties across civilisation divides to embrace the principle of tolerance in order to establish sustainable bridges across different civilisations. This trend has crept into the domain of arbitration, particularly, in cross-border commercial transactions, which require the parties to provide for the arbitration clause in their contracts. To this end, this paper examines the way and manner in which Islamic law regards the appointment of a non-Muslim arbitrator in arbitral proceedings. It considers the relevant juristic opinions as well as the practical realities of the modern world. The statutory provisions of the arbitration laws of 18 Muslim countries are examined with a view to identifying any restriction in the appointment of a non-Muslim as an arbitrator. The paper concludes with some recommendations that would promote cross-border transactions and international arbitration while breaking the often overstated civilisational divide.